PETATAH-PETITIH MINANGKABAU DALAM KRIYA LOGAM TEKNIK CHASING REPOSSE DAN ENGRAVING - Aldika Candra; Yovita Sandra; Ajusril . (Serupa The Journal of Art Education, 2012)
Abstract Nowadays, Minangkabunese starts to forget their own culture,especially the young generation of Minang who gets influenced by many cultures.This works is aimed to remind young generation of Minang abauat the custm of Minang culture, and also to give new horizon or new idea metal skill chasing repose and engraving technigue final project there are ten works produced,entitlet, 1) alam takambang jadi guru, 2) aia janiah salangko landai, ikan jinak sulik dijangkau, 3) kalawik riak mahampeh, kapulau riak mamutuih, 4) mati samuik karano manisan, 5) aia didaun keladi, 6) itiak pulang patang, 7) kalau talia kaia panjang sajangka, lawik dalam susah diduga, 8) kuek dari paga basi, kokoh nan dari paga tembok, 9) managakkan banang basah, 10) pasa jalan dek batampuah. While working on these works, the writer finds some obstacles, they art : 1) in working process, while combining the two technicues used, the writer has to think abaout part of work seriously. 2) in finishing the work, writer often changes the materialin coloring the metal  skill in order o get an appoprate color and agreed by the adusors. Kata kunci : Alam , Guru , Petatah Petitih, logam